Neuroinflammation and acute ischemic stroke: impact on translational research and clinical care - Levinson, Simon; Pulli, Benjamin; Heit, Jeremy J. (Frontiers in Surgery, 2025)
BackgroundStroke, encompassing both ischemic and hemorrhagic subtypes, is a leading cause of mortality and disability globally and current treatments remain limited. Neuroinflammation plays a crucial role in the pathophysiology of stroke, influencing both acute injury and long-term recovery.ObjectiveThis review aims to provide a comprehensive overview of neuroinflammation in stroke, detailing the mechanisms, clinical implications, and potential therapeutic strategies.MethodsA detailed literature review was conducted, focusing on recent advancements in understanding the neuroinflammatory processes in stroke, including the roles of thromboinflammation, blood-brain barrier (BBB) disruption, and the immune response.ResultsThe initial ischemic insult triggers an inflammatory cascade involving both innate and adaptive immune responses. BBB disruption allows peripheral immune cells and neurotoxic substances to infiltrate the brain, exacerbating neuronal damage and increasing the risk of infections such as pneumonia and urinary tract infections. Thromboinflammation, characterized by platelet activation and immune cell interactions, further complicates the ischemic environment. Proteomic studies have identified key biomarkers that offer insights into neuroinflammatory mechanisms and potential therapeutic targets. Advances in imaging techniques, such as PET and MRI, enable real-time monitoring of neuroinflammation, facilitating personalized treatment approaches.ConclusionNeuroinflammation significantly impacts stroke outcomes, presenting both challenges and opportunities for treatment. Current immunologic therapeutic strategies are limited. Future research should aim to further elucidate the complex immune interactions in stroke, refine imaging biomarkers for clinical use, and develop effective interventions to mitigate neuroinflammation.